Isolation and Partial Characterization of a New Lectin from Seeds of the Greater Celandine (Chelidonium majus) - Peumans, Willy J. (1985)
Seeds of the greater celandine (Chelidonium majus L.) contain a lectin which could be isolated using a combination of affinity chromatography on chitin and ion exchange chromatography on sulphopropyl-Sephadex. The purified lectin was partially characterized with respect to its biochemical and physicochemical properties. It is a small dimeric protein composed of two different subunits of M(r) 9,500 and 11,500, respectively. Its amino acid composition is typified by high contents of glycine and cysteine. No covalently bound carbohydrate could be detected. Hapten inhibition experiments indicated that the lectin exhibits specificity towards oligomers of N-acetylglucosamine, the potency of inhibition increasing with chain length up to four residues. The greater celandine lectin is the first lectin to be isolated from a species belonging to the plant family Papaveraceae (poppy family). Although it represents a new type of plant lectin, resemblances to phytohemaglutinins from diverse taxonomic origin are obvious.